Application Of FMEA Method In Halal Risk Determination On Halal Poultry Slaughtering Operations - Mohd Hasli Ramli; Arieff Salleh Rosman; Mohammad Aizat Jamaludin (Universiti Sains Islam Malaysia, 2024)
Indexed by Scopus